EXTENSÃO AUTOADJUNTA DO HAMILTONIANO DO SISTEMA DE AHARONOV-BOHM COM MOMENTO MAGNÉTICO ANÔMALO - Costa, Ramon Francescolli (2016)
In this work we present the Aharonov-Bohm effect, as well as its implications. We also present the self-adjoint extension, an important tool in quantum mechanics. This work's main objective is to investigate the relation between the self-adjoint extension parameter and the Aharonov-Bohm system's parameters. Of particular interest is the relation between the self-adjoint extension parameter and the electron's anomalous magnetic dipole moment. This is done by comparison between two self-adjoint extension methods: Bulla-Gesztesy's and Kay-Studer's. We obtain the mathematical relation between the aforementioned quantities and conclude that the chosen methods are suitable to accomplish our goals.